Management of Character Education in School: A Literature Review - Annisa Tasya Marsakha; Hasan Hariri; Sowiyah Sowiyah (Universitas Kristen Satya Wacana, 2021)
Character education is an effort to strengthen and improve the nation's moral or ethical values, especially students who will become the nation's next generation and spearhead the success of a nation with honorable character. The state is responsible for this by preserving the noble values that have been possessed by our ancestors before, where these values are a way to unite the diversity of the Indonesian people, from ethnicity, race and religion. The character education management in school is one way to anticipate and minimize the nation's moral decline which is a problem in the world of education, especially in Indonesia. This research purpose to identify the management of character education in school. This research is literature review research. A Literature review of literature was used to obtain articles from online databases relevant to the management of character education in school from 2015-2020. The results of the 22 articles reviewed are the management of character education requires cooperation between teachers, the entire school community, parents, society, so that what has been determined can be realized, namely students who have and instill moral values in life.